Needs Analysis of “SIGADIS” Diorama Media for Enhancing Water Cycle Understanding in Grade IV Islamic Elementary Schools in Indonesia - Aisyatul Nabilla, Khansa; Ibda, Hamidulloh (JENTRE, 2025)
This study aims to analyze the need for "SIGADIS" (Simple Diorama Water Movement Cycle) learning media in science learning for grade IV MI/SD, especially on the water cycle material. The approach used is quantitative with a cross-sectional survey method, involving 10 students and 5 teachers from schools in Kranggan District. The instrument used is a questionnaire. The results of the study indicate that students' needs for the "SIGADIS" learning media are very high, with 14 out of 15 aspects being in the "very need" category. Students consider that this media is able to make learning more interesting, interactive, and effective in explaining the concept of the water cycle. In addition, all teachers also showed a high need for this media, especially in terms of training, design, and use of learning media. In conclusion, the "SIGADIS" learning media is very much needed to improve the quality of learning, motivate students, and facilitate understanding of the concept of the water cycle. Therefore, the development and implementation of this media are priorities to support more effective and enjoyable learning.